Repeatability of ultrashort echo time‐based two‐component T2* measurements on cartilages in human knee at 3 T. Issue 6 (3rd October 2012) - Qian, Yongxian; Williams, Ashley A.; Chu, Constance R.; Boada, Fernando E.
Abstract: Repeatability of in vivo measurement of multicomponent T 2 * relaxation in articular cartialges in human knee is important to clinical use. This study evaluated the repeatability of two‐component T 2 * relaxation on seven healthy human subjects. The left knee was scanned once a day in three consecutive days, on a clinical 3T MRI scanner with eight‐channel knee coil and ultrashort echo time pulse sequence at 11 echo times = 0.6–40 ms. The intrasubject and intersubject repeatability was evaluated via coefficient of variation (CV = standard deviation/mean) in four typical cartilage regions: patellar, anterior articular, femoral, and tibial regions. It was found that the intrasubject repeatability was good, with CV < 10% for the short‐ and long‐ T 2 * relaxation time in the layered regions in the four cartilages (with one exception) and CV < 13% for the component intensity fraction (with two exceptions). The intersubject repeatability was also good, with CV ∼8% (range 1–15%) for the short‐ and long‐ T 2 * relaxation time and CV ∼10% (range 2–20%) for the component intensity fraction. The long‐ T 2 * component showed significantly better repeatability (CV ∼8%) than the short‐ T 2 * component (CV∼12%) ( P < 0.005). These CV values suggest that in vivo measurement of two‐component T 2 * relaxation in the knee cartilages is repeatable on clinical scanner at 3 T, with a signal‐to‐noise ratio of 90. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.